2023
DOI: 10.3389/fnhum.2022.912440
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation patterns and muscle synergies reflect different modes of coordination during upper extremity movement

Abstract: A core issue in motor control is how the central nervous system generates and selects the muscle activation patterns necessary to achieve a variety of behaviors and movements. Extensive studies have verified that it is the foundation to induce a complex movement by the modular combinations of several muscles with a synergetic relationship. However, a few studies focus on the synergetic similarity and dissimilarity among different types of movements, especially for the upper extremity movements. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…According to the analysis, the ED, ECR, ECU and B muscles are specific synergy modules of WE, while the FCR, PL and FDS are specific synergy modules of WF. BB was a shared-muscle synergy module, which supports wrist flexion and extension and maintains the stability of the upper limb [18]; this conclusion is consistent with the results of studies on muscle activation and muscle synergism in different movement modes of the upper limb [40]. It was found that the action potentials used to produce various movements were different.…”
Section: Shared and Specific Synergysupporting
confidence: 85%
See 1 more Smart Citation
“…According to the analysis, the ED, ECR, ECU and B muscles are specific synergy modules of WE, while the FCR, PL and FDS are specific synergy modules of WF. BB was a shared-muscle synergy module, which supports wrist flexion and extension and maintains the stability of the upper limb [18]; this conclusion is consistent with the results of studies on muscle activation and muscle synergism in different movement modes of the upper limb [40]. It was found that the action potentials used to produce various movements were different.…”
Section: Shared and Specific Synergysupporting
confidence: 85%
“…For the feature analysis of muscle coordination, previous studies mainly extracted and analyzed the spatio-temporal features of muscle coordination based on non-negative matrix decomposition. Xiao L et al introduced the non-negative matrix factorization (NMF) method to explore the muscle activation patterns and synergy structure under six types of movements [40]. De Marchis C et al analyzed the distribution of neural actuations among muscles that work together during the execution of a free-pedal task based on non-negative matrix factorization [17].…”
Section: Space-frequency-time Characteristics Of Muscle Synergymentioning
confidence: 99%
“…The preprocessing of sEMG signals involved several steps. First, a Butterworth high-pass filter with a cutoff frequency of 40 Hz was applied to the acquired sEMG signals ( Chen et al, 2023 ). Next, a 50 Hz notch filter was used to remove powerline interference.…”
Section: Methodsmentioning
confidence: 99%
“… Tang et al (2014) applied Pearson correlation analysis on muscle synergy among different healthy subjects executing similar tasks revealed a correlation coefficient of up to 0.85. Chen et al (2023) identified shared and specific synergies in six upper limb actions, forming a basis for the muscle synergy theory. Brambilla and Scano (2022) utilized experimental and simulated data to investigate the influence of the number of muscles on the structure and quantity of synergies.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the high number of degrees of freedom, it would cause an extremely heavy burden on the CNS if the muscles were individually controlled. One common opinion proposes that the CNS controls the muscles through a linear combination of neuromotor building blocks named muscle synergies to reduce the computational complexity [1][2][3][4][5][6][7]. Muscle synergies are defined as sets of muscles coordinately activated that work as a fixed combination [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%